The effects of service quality towards customer satisfaction of Islamic Bank in Kuantan Pahang /Maz Izuan Mazalan, Faresya Zunaida Mohd Zubair and Prof Madya Dr. Rozman Mohd Yusof - Mazalan, Maz Izuan; Mohd Zubair, Faresya Zunaida; Mohd Yusof, Rozman (2015)
The goal of this study is to identify the effects of Service Quality (SERVEQUAL) towards customer satisfaction at Islamic Bank in Kuantan, Pahang. The study also aims to examine the relationship between Service Quality (Reliability, Tangibility and Responsiveness) and Customer Satisfaction, to investigate the most influencing factor of Service Quality provided at Islamic Bank in Kuantan area. A sample of 103 banking customers was drawn from Islamic Bank in Jalan Tun Ismail, Kuantan, Pahang. The questionnaire was developed for this study based on SERVEQUAL model that identified the three (3) from the basic five (5) dimensions of SERVEQUAL in banking service environments on customer satisfaction. At the end, the results should indicate which SERVEQUAL dimensions have positive or negative influence on customer satisfaction.